Sitematización de la primera etapa del currículo de la Facultad de Odontología de la Universidad de Antioquia. Noviembre 1993- octubre 1995 - Beltrán-Salazar, Magda; Sierra-Lopera, Jorge Luis; Posada-de Castaño, Patricia; Valencia-Ramírez, Consuelo; Pineda-Suárez, Adrián Leandro (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The School of Dentistry of the University of Antioquia began the development of an alternative curricular proposal called Curricular Transformation at the beginning of 80s, looking for the integral education of dentists as a part of a whole life personal, social, and professional project. Curricular Transformation understands Dental Practice as the scientific, technical and social response to real needs of communities, including but not limited to clinical aspects of practice. In turn, it understands Dentistry’s objet of study as the Human Health-Disease Process, emphasizing on its oral component. The first group of students in the Curricular Transformation began to study at the School in November 1993. Evaluation of the project is an integral part of Curricular Transformation. That is why a systematization of the experience of organization, formation and participation of teachers, students, and administrative personnel of the School was carried out, within a historical hermeneutic, ethnographic approach. It was the purpose of the study to document and offer an interpretation the experience of the first group of students in the Curricular Transformation as they cursed their first three semesters at the University, considered as a first stage of Study Plan for Dentists in the School. There were held two workshops with teachers and students to gather an validate that experience, using a previous reconstruction of facts based upon documents, videos and reports of each one of the semesters of the first stage. Descriptive analysis showed administrative failures related to educational aspects of teachers, deficiencies in the evaluation of learning, and in didactical methodologies used. In the other hand, they stood out as positive aspects human and research developments, and autoevaluation abilities, these are all important aspects of Curricular Transformation conception. Structural analysis led to define the reconstruction of the curricular process, showing its weakness and its possibilities of improvement Inferential analysis led to the conclusion that failures were the result of hurry for the implementation, leading to improvisation, disorganization, higher resistance to change, and to inadequate coordination. It is recognized as a valuable aspect of experience the responsibility of a few highly- compromised ones, who knew how to implement the curricular proposal in spite of adversity, but did not were able to contaminate their enthusiasm to the whole faculty.